2008
DOI: 10.1086/592254
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsia parkeriRickettsiosis and Its Clinical Distinction from Rocky Mountain Spotted Fever

Abstract: Closer attention to the distinct clinical features of the various spotted fever syndromes that exist in the United States and other countries of the Western hemisphere, coupled with more frequent use of specific confirmatory assays, may unveil several unique diseases that have been identified collectively as Rocky Mountain spotted fever during the past century. Accurate assessments of these distinct infections will ultimately provide a more valid description of the currently recognized distribution, incidence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
220
1
13

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(242 citation statements)
references
References 38 publications
8
220
1
13
Order By: Relevance
“…The three patients of the present study showed clinical improvement without been treated with specific antibiotics (tetracyclines or chloramphenicol) that are usually recommended to treat rickettsiosis 2 . This condition is in accordance with previous reported cases of acute rickettsiosis due to R. parkeri in the United States, characterized by clinical manifestations that resolved even in the absence or delay treatment with specific antibiotics 13 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The three patients of the present study showed clinical improvement without been treated with specific antibiotics (tetracyclines or chloramphenicol) that are usually recommended to treat rickettsiosis 2 . This condition is in accordance with previous reported cases of acute rickettsiosis due to R. parkeri in the United States, characterized by clinical manifestations that resolved even in the absence or delay treatment with specific antibiotics 13 .…”
Section: Discussionsupporting
confidence: 92%
“…The three cases also presented similar pattern in the serological reactivities to different rickettsial antigens, characterized by higher and similar titers to R. parkeri and R. rickettsii, and substantially lower titers to other rickettsial antigens, including the spotted fever group agents R. felis, R. amblyommii, and R. rhipicephali. Similarly, human cases of R. parkeri infection in the United States showed similar IFA titers to R. parkeri and R. rickettsii 13 . The three patients of the present study showed clinical improvement without been treated with specific antibiotics (tetracyclines or chloramphenicol) that are usually recommended to treat rickettsiosis 2 .…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Symptoms develop a median of 5 days (range: 2-10 days) after the bite of an infected tick (39). The first manifestation in nearly all patients is an inoculation eschar (a dark, scabbed plaque overlying a shallow ulcer, typically 0.5-2 cm in diameter), which generally is nonpruritic, nontender or mildly tender, and surrounded by an indurated, erythematous halo and occasionally a few petechiae (Figure 24).…”
Section: Rickettsia Parkeri Rickettsiosismentioning
confidence: 99%
“…The first manifestation in nearly all patients is an inoculation eschar (a dark, scabbed plaque overlying a shallow ulcer, typically 0.5-2 cm in diameter), which generally is nonpruritic, nontender or mildly tender, and surrounded by an indurated, erythematous halo and occasionally a few petechiae (Figure 24). The presence of more than one eschar has been described (39). Fever typically develops within a few days of the eschar.…”
Section: Rickettsia Parkeri Rickettsiosismentioning
confidence: 99%